ANALISIS ANTROPOMETRI TERHADAP KEBERHASILAN SHOOTING 3 POIN PADA PEMAIN BOLABASKET - Risky Tm, ; Himawan Wismanadi, (Ordik, 2012)
The aim of this research was to described of anthropometrical analysis to make succeed  in 3 point shooting of basketball players.  There are many fundamental skills  should be mastered to the basketball players, namely: ball handling, passing and catching, dribbling, shooting, pivot moving, rebound, lay up shoot, stopping, fake and faints, and tipping. Anthropometric components may were contributing to the success of doing shooting, so the individual anthropometric was analyzed because of its importance to success in basketball.  Shoot or shooting is a decisive element in winning the game, because winning is determined by the number of balls into the basket. In this study using a shooting 3 points, 3 points for shooting distance farther than the score 2 points or 1 point.    In doing the shooting, there are components of anthropometric (human body size) are used effects are: Height, leg length and arm length. Anthropometrics The term is also known in the field of sports, which is a measurement of knowledge concerning the human body, particularly to measure the dimensions of the body. From these measurements, then in getting results which will be used to create or determine what size should be used to test the research, which will be used by researchers to test the researchThe problem of this research was, what are the role of these components  of anthropometrics to make success in basketball. Each subject was measured of the anthropometric components, and they should take  shooting 3 points. The results showed that anthropometry associated with shooting 3 (three) points is the height, long legs and long arms. The tools used in the study was measuring instruments in accordance with the procedures of research, i.e..measuring devices that have been in tera. In a shooting test 3 (three) points is expected to research can work well, effective, convenient, safe, healthy, and efficient. And to be able to design a training pattern shooting for a basketball team. Based on the research ideal anthropometric composition of the data we obtain for the average size of 67 cm arm length, leg length 42 cm, and height 166 cm. The best size is the result of some other subject size. While classified as bad is the average size of 76 cm arm length, leg length 47 cm, and height 179 cm. However, if a player has a length above the average to achieve good results, can also shoot 3 points by trained intensively, basketball players will achieve good results as well.